Proposed upgrading handicrafts gallery at No 21B Medan Istana 3, Bandar Ipoh Raya, 30000 Ipoh, Perak for Yayasan Orang Asli Perak (YOAP) / Atiqah Azlan - Azlan, Atiqah (2012)
All final student of Diploma in Interior Architecture should be completed every stage of their final design. This is to analysis towards students knowledge about interior design from basic to the final presentation in board. Proposed upgrading of handicraft gallery for Yayasan Orang Asli Perak (YOAP) at Bandar Ipoh Raya, Ipoh Perak has being chosen for this final project. This is because, YOAP gallery being one of the place that includes to the lists of Visit Perak 2012. Besides, the clients also have an intention to upgrade the office and the gallery to introduce the Orang Asli handicrafts products in the markets. The concept and image that used for this gallery must be reflect with clients needed and Orang Asli culture. Besides, through interview observation media, internet and case study, some of the information can be used to finish this project.